DE AMARNA AOS RAMSÉS - Cardoso, Ciro Flamarion (PHOÎNIX, 2020)
This text attempts a reappraisal of a very controversial period of Egypt's New Kingdom history, from the Amarna age to the beginning of the Ramesside era (XIVth-X111th centuries BC), by discussing the abundant new research material published these last years. It will be shown that, in spite of much new knowledge, differences of opinion are still rife, in special those concerning Akhenaton's reign and the sense of his reforms.